DAMPAK DISIPLIN BELAJAR DAN KONSEP DIRI DALAM PRESTASI BELAJAR KOGNITIF SEKOLAH MENENGAH KEJURUAN - Rizky, Try Moehammad; Muhidin, Sambas Ali (Jurnal Pendidikan Manajemen Perkantoran (JPManper), 2017)
Cognitive learning achievements of students are influenced by many factors, including the discipline of learning and self-concept of students. Research on both the variables, i.e. learning discipline and self-concept much done, either partially or review examines both in the analysis of the relationship (correlation). One of them is this study that tries to present the results of research regarding the influence of the discipline of learning and the concept of cognitive learning achievements themselves against students in Private Vocational School located in the city of Greenacres. This study used a survey method, while data collected through questionnaire against 52 people grade XI Department Administration offices, analyzed through double regression data analysis techniques, that is, to find out whether there are significant effects between the discipline of learning and the concept of cognitive learning achievements of his students. Results of the study indicate that there is an influence of the discipline of learning and the concept of cognitive learning achievements themselves against significant students in Private Vocational School in Cimahi.ABSTRAKPrestasi belajar kognitif siswa dipengaruhi oleh banyak faktor, diantaranya disiplin belajar dan konsep diri siswa. Penelitian tentang kedua variabel tersebut, yaitu disiplin belajar dan konsep diri banyak dilakukan, baik yang mengkaji secara parsial maupun mengkaji keduanya dalam analisis hubungan (korelasi). Salah satunya adalah kajian ini yang mencoba menyajikan hasil penelitian mengenai pengaruh disiplin belajar dan konsep diri terhadap prestasi belajar kognitif siswa pada SMK Swasta yang berlokasi di Kota Cimahi. Penelitian ini menggunakan metode survei, sementara data yang dikumpulkan melalui kuesioner terhadap 52 orang siswa kelas XI Jurusan Administrasi Perkantoran, dianalisis melalui teknik analisis data regresi ganda, yaitu untuk mengetahui apakah terdapat pengaruh yang signifikan antara disiplin belajar dan konsep diri terhadap prestasi belajar kognitif siswa. Hasil kajian menunjukan bahwa terdapat pengaruh disiplin belajar dan konsep diri terhadap prestasi belajar kognitif siswa yang signifikan pada SMK Swasta di Kota Cimahi.